Business-Level Strategy for the Foreign Commercial Banks operating within Malaysia - Rasool Khan, Mohamed Rizal (2007)
This paper discusses the strategic positioning and use of Porter’s (1980) generic strategy framework within the foreign commercial banks operating in Malaysia. It was found that two distinct strategic groups were formed by the foreign commercial banks. Performance analysis conducted suggests that banks with clearer strategic direction managed to outperform its peers in its strategic group. Furthermore, the performance of one strategic group was significantly lower than that of the second.